The Croatian possessive adjective as the antecedent of a relative pronoun - Ivan Marković (Rasprave: Časopis Instituta za Hrvatski Jezik i Jezikoslovlje, 2008)
The ability of Croatian possessive adjectives (PA) to control relative pronouns is here taken under consideration. This ability is weakening in Slavic languages (in some of them it has been completely lost), i. e. in such constructions PA is replaced by an adnominal genitive. Attested examples of relative clauses with a PA-antecedent show that, at least in written Croatian, PAs are still able to control relative pronouns. Three-quarters of contemporary Croatian speakers reject constructions where a PA controls a relative pronoun. However, these constructions are found in texts, and only a few speakers do not find them unacceptable. The typologically uncommon characteristics of relative clauses with PA-antecedents are analyzed, especially the fact that PAs controlling relative pronouns behave like inflected forms, and not like derived forms, which they undoubtedly are.